2019
DOI: 10.1007/s11906-019-0977-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Maternal Brain Alterations in Preeclampsia: the Need for a Multidisciplinary Effort

Abstract: Porpuose of Review: To provide insight into the mechanisms underlying cerebral pathophysiology in preeclampsia and to highlight possible methods for evaluation, screening and surveillance of cerebral complications in the condition. Recent Findings: Every 12 minutes, a woman dies as a consequence of preeclampsia with cerebral complications, such as eclampsia, among the most common causes. The incidence of eclampsia has been estimated to vary from one in 100 to one in 2000 deliveries, with the highest incidences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 102 publications
(103 reference statements)
0
22
0
Order By: Relevance
“…Headache is a high-risk factor for RPLS and a precursor of eclampsia. Cortical blindness is also a unique manifestation of RPLS [ 11 , 14 , 15 ]. This study found that in preeclampsia, neurological symptoms such as headache ( P < 0.05) was independent risk factors for RPLS, but the blurred vision is also a potential factor that cannot be ignored (The p value 0.072 is close to 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Headache is a high-risk factor for RPLS and a precursor of eclampsia. Cortical blindness is also a unique manifestation of RPLS [ 11 , 14 , 15 ]. This study found that in preeclampsia, neurological symptoms such as headache ( P < 0.05) was independent risk factors for RPLS, but the blurred vision is also a potential factor that cannot be ignored (The p value 0.072 is close to 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent seizures can lead to hypoxia, maternal injury, aspiration pneumonia, and status epilepticus. While the incidence of eclampsia is 1 in 2000 in high-income countries, it is estimated to be 1 in 100 to 1 in 1700 deliveries in low-and middle-income countries [11].…”
Section: Preeclampsia (Pee)mentioning
confidence: 99%
“…Recent studies show promising results on the detection of cerebral biomarkers (S100B, neuron-specific enolase (NSE), neurofilament light chain (NfL), and tua) to diagnose cerebral complications at onset or before onset of preeclampsia [11].…”
Section: Cerebrovascular Complications Of Hypertension In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial dysfunction at the bloodbrain barrier level along with or resulting in cerebral blood flow alteration is a leading theory. 7 Studies using transcranial Doppler (TCD) ultrasound have consistently shown increased cerebral perfusion pressure (CPP) in PE, although with large variances within groups. 8e11 Dynamic cerebral autoregulation (DCA) is a physiological process that maintains cerebral blood flow relatively constant despite changes in blood pressure (BP).…”
Section: Introductionmentioning
confidence: 99%